Brokering Community Engagement: Proactive Strategies for Supporting Indigenous Australians with Mental Health Problems. (1st December 2016) - Sayers, Jan Maree; Hunt, Glenn E.; Cleary, Michelle; Burmeister, Oliver K.
Abstract : This qualitative study explored the experiences of mental health employees working with Indigenous clients living with mental illness. Interviews were conducted with 20 mental health workers to identify strategies they adopt to facilitate community engagement with Indigenous clients. Using a thematic analysis approach, 'Brokering community engagement' was the umbrella theme from which two subthemes related to community engagement for the service and clients emerged (1) enabling connections –community and family; and (2) recovery and reconnecting with community. Participant insights enabled a deeper understanding of the role of community in the recovery process for Indigenous clients and highlight the importance of community engagement as a primary, yet multifaceted strategy used by mental health workers in the communities they serve.